Reconstruction of Administrative Fine on Population Administration in Regional Regulation - Khaerudin, Ariy; Suharno, Suharno (Fakultas Hukum Universitas Islam Batik Surakarta, 2024)
Law Number 24 of 2013 Concerning Amendment to Law Number 23 of 2006 on Population Administration provides a burden based on â€œActive Stelselâ€ registration principle. This means that the registrar who must proactively record residence document. However, population registration dealing with the provision of administrative fines to residents who are late in registering their population documents. Inconsistency between principle and the norm raises a number of issues in their implications, especially on the regulation of fines as administrative sanctions. Disharmony between principles and norms in the administrative fine of population still regulated in the regional regulations and cause problems in its application both for local government and the population. This research aims to reconstruct regional regulation on administrative fine that should be determined for legal certainty.Based on the principles in the formulation of legislation by synchronizing and harmonizing to achieve orderly system. By Law Number 12 of 2011 Concerning the Drafting of Legislation regulates that the provisions of the higher Law should be guided by the lower regulations. Therefore, a local regulation should not conflict with higher regulations.